High resolution x-ray absorption and emission spectroscopy of LixCoO2 single crystals as a function delithiation. (31st January 2017) - Simonelli, L; Paris, E; Iwai, C; Miyoshi, K; Takeuchi, J; Mizokawa, T; Saini, N L
Abstract: The effect of delithiation in Li x CoO2 is studied by high resolution Co K-edge x-ray absorption and x-ray emission spectroscopy. Polarization dependence of the x-ray absorption spectra on single crystal samples is exploited to reveal information on the anisotropic electronic structure. We find that the electronic structure of Li x CoO2 is significantly affected by delithiation in which the Co ions oxidation state tending to change from 3+ to 4+. The Co intersite (intrasite) 4 p –3 d hybridization suffers a decrease (increase) by delithiation. The unoccupied 3 d t 2 g orbitals with a 1 g symmetry, containing substantial O 2 p character, hybridize isotropically with Co 4 p orbitals and likely to have itinerant character unlike anisotropically hybridized 3 d e g orbitals. Such a peculiar electronic structure could have significant effect on the mobility of Li in Li x CoO2 cathode and hence the battery characteristics.